Selective Effects of Psychotherapy on Frontopolar Cortical Function in PTSD. - Fonzo, Gregory A.; Goodkind, Madeleine S.; Oathes, Desmond J.; Zaiko, Yevgeniya V.; Harvey, Meredith; Peng, Kathy K.; Weiss, M. Elizabeth; Thompson, Allison L.; Zack, Sanno E.; Mills-Finnerty, Colleen E.; Rosenberg, Benjamin M.; Edelstein, Raleigh; et al. (American Journal of Psychiatry, 2017)
Objective: Exposure therapy is an effective treatment for posttraumatic stress disorder (PTSD), but a comprehensive, emotion-focused perspective on how psychotherapy affects brain function is lacking. The authors assessed changes in brain function after prolonged exposure therapy across three emotional reactivity and regulation paradigms.Method: Individuals with PTSD underwent functional MRI (fMRI) at rest and while completing three tasks assessing emotional reactivity and regulation. Individuals were then randomly assigned to immediate prolonged exposure treatment (N=36) or a waiting list condition (N=30) and underwent a second scan approximately 4 weeks after the last treatment session or a comparable waiting period, respectively.Results: Treatment-specific changes were observed only during cognitive reappraisal of negative images. Psychotherapy increased lateral frontopolar cortex activity and connectivity with the ventromedial prefrontal cortex/ventral striatum. Greater increases in frontopolar activation were associated with improvement in hyperarousal symptoms and psychological well-being. The frontopolar cortex also displayed a greater variety of temporal resting-state signal pattern changes after treatment. Concurrent transcranial magnetic stimulation and fMRI in healthy participants demonstrated that the lateral frontopolar cortex exerts downstream influence on the ventromedial prefrontal cortex/ventral striatum.Conclusions: Changes in frontopolar function during deliberate regulation of negative affect is one key mechanism of adaptive psychotherapeutic change in PTSD. Given that frontopolar connectivity with ventromedial regions during emotion regulation is enhanced by psychotherapy and that the frontopolar cortex exerts downstream influence on ventromedial regions in healthy individuals, these findings inform a novel conceptualization of how psychotherapy works, and they identify a promising target for stimulation-based therapeutics.